Establishing wildflower meadows in anthropogenic landscapes - Bretzel, Francesca; Vannucchi, Francesca; Pezzarossa, Beatrice; Paraskevopoulou, Angeliki; Romano, Daniela (Frontiers in Horticulture, 2024)
In anthropized sites, the establishment and management of sustainable and nature-based wildflower meadow solutions exclude fertilization, weeding, and watering, and reduce the frequency of mowing. Once such inputs have been reduced, the ecosystem services generated by the vegetation result in an increase in biodiversity in terms of plant and animal species, an improvement in soil quality and biota, the mitigation of air pollutants and carbon sequestration, as well as a reduction in soil temperature. Environmental education and citizen science are also some of the benefits of this type of vegetation, especially in urban areas. Herbaceous meadow-like communities, which are composed of forbs only or a combination of graminoid and forb species, are usually established by sowing. The seeds are available for purchase from specialized seed producers as single species or in a mix, some companies offer mixes composed of garden species with botanical species. Donor meadows are the sources of the genetic material and the template to reproduce the meadow herbaceous community at different sites through seed harvest, hay harvest, and the displacement of soil with its seed bank. Management techniques, such as soil preparation, determining the appropriate sowing and mowing time, can help in establishing and maintaining the most desirable species. The suspension of urban turf mowing allows the growth of the natural seed bank, which in unproductive soils facilitates the appearance of many pollinator-friendly herbaceous species. With the appropriate pedological conditions and management, the natural urban herbaceous vegetation thus provides beautiful and rich plant communities, which are also easy to maintain. This review identifies the best practices through a qualitative selection of case studies related to the various methods to establish wildflower meadows in the urban infrastructure and the main constraints such as the lack of a suitable seed market.